2004
DOI: 10.1152/ajpendo.00348.2003
|View full text |Cite
|
Sign up to set email alerts
|

Forearm vascular control during acute hyperglycemia in healthy humans

Abstract: The vascular endothelium is a site of pathological changes in patients with diabetes mellitus that may be related to severe chronic hyperglycemia. However, it is unclear whether transient hyperglycemia alters vascular function in an otherwise healthy human forearm. To test the hypothesis that acute, moderate hyperglycemia impairs endothelium-dependent forearm vasodilation, we measured vasodilator responses in 25 healthy volunteers (11 F, 14 M) assigned to one of three protocols. In protocol 1, glucose was vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 32 publications
4
29
0
1
Order By: Relevance
“…Other laboratories have reached opposite conclusions. Houben et al [16], with the use of a very similar protocol (local hyperglycaemia of about 15 mmol/l), failed to find differences in forearm microvessel and resistance vessel reactivity to ACh, SNP, norepinephrine or NO synthase inhibition, despite extending the study time to 24 h. More recently, Reed et al [21], using a very elegant study design, also concluded that in healthy participants, when the insulin response is prevented, neither 6 h of moderate hyperglycaemia (2 mmol/l above fasting values) nor glycaemic excursions reproducing the OGTT response of IGT patients are capable of depressing the forearm vascular response to ACh or SNP. Similar findings were reported by Strey et al [20] and Gudmundsson et al [9], who measured the forearm vascular response before and after a mixed meal in healthy participants and before and after improvement of metabolic control in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Other laboratories have reached opposite conclusions. Houben et al [16], with the use of a very similar protocol (local hyperglycaemia of about 15 mmol/l), failed to find differences in forearm microvessel and resistance vessel reactivity to ACh, SNP, norepinephrine or NO synthase inhibition, despite extending the study time to 24 h. More recently, Reed et al [21], using a very elegant study design, also concluded that in healthy participants, when the insulin response is prevented, neither 6 h of moderate hyperglycaemia (2 mmol/l above fasting values) nor glycaemic excursions reproducing the OGTT response of IGT patients are capable of depressing the forearm vascular response to ACh or SNP. Similar findings were reported by Strey et al [20] and Gudmundsson et al [9], who measured the forearm vascular response before and after a mixed meal in healthy participants and before and after improvement of metabolic control in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…3), is unlikely to be due to hyperglycaemia itself, since the studies using either local or systemic hyperglycaemia have not reported this effect. It may also be unrelated to hyperinsulinaemia, since neither isolated local hyperinsulinaemia [27] nor intravenous insulin infusion [21] have been shown to affect the vascular response to SNP; however, no study to date has evaluated this response after glucose ingestion. The smaller and less persistent decline in maximal response to SNP observed when glucose was given intravenously (fasting, 651±111; 60 min, 510±88; 120 min, 545±90; 180 min, 671±121%) vs orally (fasting, 760±127; 60 min, 631±89; 120 min, 545± 90; 180 min, 549±71%) suggests that factors related to gastro-intestinal stimulation are involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No estudo de Eicke et al 18 , também não se demonstrou redução da velocidade de fl uxo pós-prandial neste mesmo leito vascular, embora avaliando pacientes fora do período gestacional. Estudos mais recentes que utilizaram a infusão intravenosa de glicose também em indivíduos não gestantes não puderam demonstrar alteração doplervelocimétrica, mesmo avaliando vasos de menor diâmetro, tais como na artéria braquial 19 , na artéria da retina em estudo realizado em animal 20 ou mesmo nas artérias coronárias 21 , o que faz concluir que a forma aguda ou moderada de hiperglicemia não é capaz de alterar a resposta vascular.…”
Section: Antes Da Glicoseunclassified